Modeling the anaerobic digestion of cane-molasses vinasse: Extension of the Anaerobic Digestion Model No. 1 (ADM1) with sulfate reduction for a very high strength and sulfate rich wastewater. (15th March 2015) - Barrera, Ernesto L.; Spanjers, Henri; Solon, Kimberly; Amerlinck, Youri; Nopens, Ingmar; Dewulf, Jo
Abstract: This research presents the modeling of the anaerobic digestion of cane-molasses vinasse, hereby extending the Anaerobic Digestion Model No. 1 with sulfate reduction for a very high strength and sulfate rich wastewater. Based on a sensitivity analysis, four parameters of the original ADM1 and all sulfate reduction parameters were calibrated. Although some deviations were observed between model predictions and experimental values, it was shown that sulfates, total aqueous sulfide, free sulfides, methane, carbon dioxide and sulfide in the gas phase, gas flow, propionic and acetic acids, chemical oxygen demand (COD), and pH were accurately predicted during model validation. The model showed high (±10%) to medium (10%–30%) accuracy predictions with a mean absolute relative error ranging from 1% to 26%, and was able to predict failure of methanogenesis and sulfidogenesis when the sulfate loading rate increased. Therefore, the kinetic parameters and the model structure proposed in this work can be considered as valid for the sulfate reduction process in the anaerobic digestion of cane-molasses vinasse when sulfate and organic loading rates range from 0.36 to 1.57 kg SO 4 2 −  m −3 d −1 and from 7.66 to 12 kg COD m −3  d −1, respectively. Graphical abstract: Highlights: An extension of ADM1 for sulfate reduction was proposed, calibrated & validated. Four parameters of ADM1 & all the sulfate reduction parameters were calibrated. Nine process variables were accurately predicted during model validation. High (±10%) to medium (10%–30%) accuracy quantitative predictions were achieved. The model was considered as valid to assist the anaerobic digestion of vinasse.